STRATEGI PEMENANGAN JOKO WIDODO-KH.MA’RUF AMIN DI KOTA PEKANBARU TAHUN 2019 - Syella Agnesia Hutagalung (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Presidential election is a form of democratic party in a country to elect a head of state who will carry out state policies in one period of his leadership which later must be accountable to the people. In the 2019 presidential election, the presidential candidate Jokowi-Ma'ruf Amin lost the vote in Pekanbaru City. The defeat of Jokowi-Ma'ruf Amin in Pekanbaru did not match the vote target they wanted to achieve, which was above 50%, but in fact the votes obtained by the presidential candidate Jokowi-KH.Ma'ruf Amin were only 26.37%. The purpose of this study was to find out what strategies were carried out by the winning team for the city of Pekanbaru and what were the factors causing the defeat of Jokowi-KH. Ma'ruf Amin in Pekanbaru City. This type of research is descriptive. The research location of the Riau Projo Winning Team office. The types and sources of research data are divided into primary data and secondary data related to the winning team's strategy.Data collection techniques used by interview and documentation. While the data analysis was carried out by qualitative analysis. The results of this study are that there are 2 strategies used, namely offensive and defensive, both of which were used by the winning team in winning the presidential and vice presidential candidates in the city of Pekanbaru. and the factor causing Jokowi-Ma'ruf Amin's defeat is that there are still many people who believe and are consumed by the hoax issue and the winning team is still unable to fully counter the issues circulating in the community and Pekanbaru is also the basis for winning Prabowo-Sandi and moreover, Sandiaga is the son of the region because born in Pekanbaru which can influence the election of the  Keywords:Strategy, Winning Team, Presidential Election